2016
DOI: 10.1111/aos.13152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal dexamethasone implant on intra‐ocular cytokines and chemokines in eyes with retinal vein occlusion

Abstract: Intravitreal dexamethasone treatment resulted in alterations in the concentrations of pro-inflammatory cytokines MCP-1 and IL17-E in patients with BRVO and MCP-1 and IL1-α in patients with CRVO. These data highlight the important role of inflammatory mediators involved in ME due to RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…19,21 Interestingly, however, some published reports found MCP-1 AH level to decrease with DEX injection for retinal vein occlusion-derived macular edema. 32 By means of the current results, we have proven MCP-1 to be directly related to MV change in DME under DEX treatment. This finding is consistent with the general understanding of the steroid effect on DME and, moreover, highlights this molecule as a crucial role-playing agent in DME.…”
Section: Discussionmentioning
confidence: 50%
“…19,21 Interestingly, however, some published reports found MCP-1 AH level to decrease with DEX injection for retinal vein occlusion-derived macular edema. 32 By means of the current results, we have proven MCP-1 to be directly related to MV change in DME under DEX treatment. This finding is consistent with the general understanding of the steroid effect on DME and, moreover, highlights this molecule as a crucial role-playing agent in DME.…”
Section: Discussionmentioning
confidence: 50%
“…The safety and efficacy profile after a second treatment with DEX implant was generally similar to that seen after the first treatment, and patients who had delayed treatment never matched the improvement of those treated earlier in the disease process [146, 147]. The ORVO study ( n = 17) also demonstrated that Ozurdex can reduce several propermeability proteins such as persephin, pentraxin 3, hepatocyte growth factor, endocrine gland VEGF, insulin-like growth factor binding proteins, and proinflammatory cytokines like MCP-1 and IL17-E [148, 149]. Also, the SHASTA study ( n = 289) demonstrated that the visual acuity and central retinal thickness significantly improved both after initial or retreatment.…”
Section: Treatmentmentioning
confidence: 96%
“…; Rezar‐Dreindl et al. ). However, the results of these studies have not been conclusive due to their retrospective nature or small sample size.…”
Section: Introductionmentioning
confidence: 99%